beta-Hemolytic streptococci and other beta-hemolytic organisms in apical periodontitis and severe marginal periodontitis - Johnson, B T; Mayo, J A; Jeansonne, B G (Endodontics & dental traumatology, 1999)
Thirteen teeth with necrotic pulps and apical periodontitis and nine severe periodontal pockets were cultured for presence of beta-hemolytic streptococci and other beta-hemolytic organisms. Samples were dispersed and plated on two non-selective and one selective growth media and incubated anaerobically and in 10% CO2 in air. A total of 59 beta-hemolytic colonies were purified and identified. Eight beta-hemolytic streptococcal isolates were obtained from three of the severe marginal periodontitis sites. All were identified as belonging to the Streptococcus sanguis group. No beta-hemolytic streptococci were detected in apical periodontitis samples. Twenty obligately anaerobic isolates were detected, all of which were known periodontal and endodontic pathogens. Isolates from apical periodontitis sites were identified as Propionibacterium acnes, Actinomyces naeslundii, Actionomyces odontolyticus and Peptostreptococcus micros, while severe marginal periodontal sites contained the same species with the addition of Actinomyces viscosus and Actinomyces meyeri. Of 19 staphylococci and micrococci, Staphylococcus epidermidis was the predominant isolate in both apical periodontitis and severe marginal periodontitis sites. However, less commonly known organisms such as Staphylococcus cohnii and Micrococcus sp. were identified in severe marginal periodontitis sites. The isolation of Bacillus sp. (12 isolates) in one severe marginal periodontitis and two apical periodontitis subjects was especially interesting, warranting consideration of this organism as a legitimate isolate and potential pathogen in oral disease.